Analysis of mathematics learning activities materials of operating skills of rapid number students in elementary school through online learning - Viki, Praditiya Alvian; Chumdari, Chumdari; Slamet, St. Y.; Adriyanto, Hardo (Universitas Islam Raden Intan Lampung, INDONESIA, 2023)
This study aims to improve mathematics learning outcomes, especially in learning fractional arithmetic operations in fifth grade students of SD Muhammadiyah 01 Paron, Ngawi Regency. In this study, offline and online learning models or what is often called Blended Learning will be implemented using case study problems. This type of research is descriptive qualitative research, the research subjects are students of class Va and class Vb Muhammadiyah Elementary School 01 Paron, totaling 19 students in class Va and 20 students from class Vb, homeroom teachers of class Va and Vb and the principal of SD Muhammadiyah 01 Paron. The object of the research is the learning outcomes of fifth grade elementary school students, especially in mathematics subjects on the material of arithmetic operations on fractions using blended learning model learning. To test the validity of the instrument in this study using data triangulation. The research data were obtained from observations, interviews and learning outcomes tests. The data obtained were analyzed descriptively quantitatively and descriptively qualitatively. The results show that the average learning outcomes of mathematics using online learning models are still not effective because many students are constrained about mathematical concepts and students' understanding of fractional numbers is still low. With this, blended learning is a learning solution for elementary school students to improve learning outcomes and improve mathematical concepts. The average mathematics learning outcomes of students who are taught using a digital-based blended learning model are 70 while the average value of students who are taught using a conventional model is 57.5, it appears that the overall implementation of the learning process in the experimental class using a digital-based blended learning model is more supportive in mastering the material than in the classroom. control using conventional learning models.